Ethnobotanical Survey of Medicinal Plants Used in the Treatment of Transmissible Diseases - Sani Halliru, Bawale; Wada, Nuraddeen; Mahmoud Dogara, Abdulrahman; Abdullahi Mahmud, Aisha; Labaran, Isah; Danlami, Hussaini (Journal of Science and Technology, 2024)
Herbal medicine, as an ancient traditional medical method, predates the establishment of contemporary healthcare systems within human culture. Globally, several groups develop their own indigenous forms of medicine and corresponding methodologies for treating and enhancing overall well-being. The research presents a comprehensive ethnobotanical survey of medicinal plants used in the treatment of transmissible diseases in Katsina State. A random selection technique was employed in conjunction with an open-ended interview guide over the period spanning from October 2022 to June 2023. The demographic information of the respondents was ascertained using Excel 2016. Quantitatively, the documented plants were subjected to analysis based on their Relative Frequency of Citation (RFC). This study identified 26 medicinal plants used in the administration and treatment of various transmissible diseases in the northern Nigerian state of Katsina. Moringa oleifera (28%) is the most frequently reported plant, followed by Olea Europaea (24%) and Azadirachta indica (20%). Leaves were the most frequently used part of the plants (69%), common method of preparation is decoction (65%). As their popularity and recognition expanded throughout the world, plants with medical potential remain the sole hope for the future. According to the current study, people of Katsina citizens had a solid awareness of the medicinal plant. Even with the progress of contemporary medicine, the people in the area still depend on using traditional plants for medical purposes.